Analysis of Factors Influencing Students’ Interest in the Islamic Religious Education Subject - Muhammad Yusuf; Khalid Abdullah Al Muzaini; Maryam Rashid Saleh Al Tamimi (Al Husna: Jurnal Ilmiah Pendidikan Agama Islam, 2025)
This study aims to analyze the factors influencing students' interest in Islamic Religious Education (PAI) subjects using a literature review method. This method involves reviewing various sources, such as journals, books, and previous research related to the topic. The factors analyzed include the role of teachers, teaching methods, school environment, family support, and peer influence. The analysis results show that the teacher's role and teaching methods significantly impact students' interest in learning PAI. Additionally, the school environment and family support also contribute to increasing or decreasing students' interest in this subject. This study is expected to serve as a reference for educators and educational institutions in designing more effective teaching strategies to enhance students' interest in PAI.